A decomposition analysis of total factor productivity growth in MENA countries: stochastic frontier analysis approach. Issue 2 (3rd July 2021) - Malik, Mushtaq Ahmad; Masood, Tariq
ABSTRACT : The present study aims to examine the output and total factor productivity (TFP) growth by estimating a stochastic frontier production function for a panel of Middle East and North Africa (MENA) countries, and to decompose TFP growth into technical change, technical efficiency, and scale efficiency. The empirical findings reveal that, while factor accumulation is the main driver of output growth in the MENA region, TFP growth is increasingly accounting for a respectable proportion of output growth, with improved technical efficiency playing a crucial role in productivity growth. Specifically, the average annual TFP growth is found to be 0.846%, with positive contributions from technical efficiency and scale efficiency. However, the results show that technical progress has had a negative impact on TFP growth. The positive growth in technical efficiency suggests that the countries are catching up towards the optimal production frontier. At a disaggregated level, oil-rich countries registered negative effects of technical progress, while non-oil countries registered negative effects of scale efficiency. Technical efficiency, however, accounts for the largest positive factor in TFP growth in both oil and non-oil country groups.